Study on the influence of intelligent human–computer interaction of AI virtual anchors on consumers’ initial trust and value co-creation behavior under the technophobia - Zhong, Linling; Wang, Yong; Yue, Zhikun; Yang, Yongzhong (Frontiers in Psychology, 2026)
IntroductionIn the context of the deep integration between artificial intelligence (AI) and e-commerce live streaming, virtual anchors have become a core interactive medium for both enterprises and consumers. However, when consumers first encounter e-commerce virtual anchors, the establishment of initial trust and the triggering of value co-creation behaviors are significantly influenced by psychological factors such as technophobia. Value co-creation behaviors encompass two dimensions: participation behavior and citizenship behavior. Technophobia in this context specifically manifests as concerns about the unknown risks of AI technology, operational complexity, and resistance to non-humanized interactions.MethodsBased on the Technology Acceptance Model (TAM), this study develops a mechanism to examine how the intelligence of human-machine interaction in e-commerce virtual anchors influences consumers’ initial trust and value co-creation behaviors, from the perspective of technophobia. To validate this model and related hypotheses, we conducted a specialized survey targeting consumers with initial exposure to e-commerce virtual anchors, collected 337 valid responses, and used Structural Equation Modeling (SEM) to test 14 research hypotheses.ResultsThe results showed that 12 hypotheses were confirmed. Specifically, the four dimensions of intelligence possessed by e-commerce virtual anchors—guidance, recognition, analysis, and feedback—all positively influence perceived usefulness and perceived ease of use. These two perceived variables further positively promote the formation of consumers’ initial trust. Regarding the impact of initial trust on value co-creation behaviors, it significantly drives consumer participation behaviors (e.g., asking questions, posting comments, following livestreaming room rules) but shows no significant effect on consumers’ citizenship behaviors (e.g., actively promoting livestreaming rooms, reporting service defects, assisting other consumers). Meanwhile, technophobia plays a significant negative moderating role in the relationship between perceived ease of use and initial trust. Two hypotheses were not supported: first, initial trust does not significantly drive citizenship behaviors, potentially due to negative cognitive legacy from early low-intelligence virtual anchors; second, technophobia does not significantly moderate the relationship between perceived usefulness and initial trust, as it primarily stems from concerns about operational complexity rather than doubts about utility.DiscussionThe findings clarify the boundary role of technophobia, particularly its key disruptive effect in the “perceived ease of use → initial trust” transformation process, thereby enriching the application dimensions of TAM in human-computer interaction scenarios. The core value of this study lies in providing empirical evidence for e-commerce enterprises to effectively build consumers’ initial trust and promote differentiated value co-creation through measures such as alleviating technophobia and optimizing virtual anchor interaction design.